Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1002/1873-3468.13553
|View full text |Cite
|
Sign up to set email alerts
|

A tale of short tails, through thick and thin: investigating the sorting mechanisms of Golgi enzymes

Abstract: The Golgi apparatus is an important site for the modification of most secreted and membrane proteins. Glycan processing is the major class of modification and is mediated by a large number of Golgi‐resident glycosyltransferases and glycosidases. These Golgi enzymes are largely type II transmembrane domain (TMD) proteins consisting of a short N‐terminal cytosolic tail, a relatively short TMD and a lumenal ‘stem/stalk’ region which acts as a spacer between the catalytic domain and the lipid bilayer. The cytosoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 105 publications
(190 reference statements)
1
72
0
Order By: Relevance
“…This increases the size of the protein preventing it from entering vesicles, leaving the Golgi. Oligomerization of sequentially acting enzymes also enhances the efficiency of glycosylation [ 18 , 19 ].…”
Section: Membrane Trafficking At the Golgimentioning
confidence: 99%
“…This increases the size of the protein preventing it from entering vesicles, leaving the Golgi. Oligomerization of sequentially acting enzymes also enhances the efficiency of glycosylation [ 18 , 19 ].…”
Section: Membrane Trafficking At the Golgimentioning
confidence: 99%
“…The remaining four mutations, including one that causes MLII (p.Ala34Pro), together with the three that cause MLIII αβ (p.Phe24Val, p.Gly26Asp, and p.Glu36Pro), impair retention in the Golgi. It has been reported that TMDs vary, depending on their organelle of residence, both in length and composition (Sharpe, Stevens, & Munro, 2010; Welch & Munro, 2019). These differences presumably impact how well the TMDs fit into the lipid bilayer of an organelle.…”
Section: Discussionmentioning
confidence: 99%
“…It seems likely that the missense mutations described here impair the ability of the mutant TMD to interact properly with the lipids of the Golgi bilayer, resulting in an unstable situation that allows the mutant protein to escape the Golgi. An alternate explanation is that the N‐terminal TMD of GlcNAc‐1‐phosphotransferase interacts with another Golgi protein to maintain its proper localization and the various mutations impair this interaction, resulting in the escape of the mutant protein from the Golgi (Schoberer et al, 2019; Sharpe et al, 2010; Welch & Munro, 2019). Further work will be required to clarify this situation.…”
Section: Discussionmentioning
confidence: 99%
“…Golgi-resident proteins are concentrated in “proper” Golgi sub-compartments by a combination of retention and retrieval mechanisms (52), but for the majority of Golgi enzymes the localization mechanisms are still enigmatic. One model proposed that the thickness of the lipid bilayer is important for the proper localization and retention of transmembrane proteins (53). Other models rely on efficient intra-Golgi and Golgi-ER recycling (54) (55).…”
Section: Discussionmentioning
confidence: 99%